2012
DOI: 10.2298/vsp1208669b
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Epley maneuver in treatment of benign paroxysmal positional vertigo of the posterior semicircular canal

Abstract: The Epley maneuver is very successful repositioning procedure in treating p-BPPV. The patients with idiopathic form p-BPPV showed higher success rate with Epley maneuver than those with secondary p-BPPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…This result differs from that of Dispenza et al (2012) and Macias et al (2000), who repeated the repositioning maneuver in the same session in case of no response, depending on the repeated test. These repetitions did not affect the rate of success compared with our work or with other studies (Wolf et al, 1999;Gans and Harrington-Gans, 2002;Roberts et al, 2006;Hunt et al, 2012;Babac and Arsovi c, 2012;Prokopakis et al, 2013). Therefore, patients with orthopedic problems (neck, back, and hip disorders), who cannot tolerate repetition of the maneuver in one session because of limitation of body movements, may be able to repeat the maneuver in more than one session to resolve the symptoms.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…This result differs from that of Dispenza et al (2012) and Macias et al (2000), who repeated the repositioning maneuver in the same session in case of no response, depending on the repeated test. These repetitions did not affect the rate of success compared with our work or with other studies (Wolf et al, 1999;Gans and Harrington-Gans, 2002;Roberts et al, 2006;Hunt et al, 2012;Babac and Arsovi c, 2012;Prokopakis et al, 2013). Therefore, patients with orthopedic problems (neck, back, and hip disorders), who cannot tolerate repetition of the maneuver in one session because of limitation of body movements, may be able to repeat the maneuver in more than one session to resolve the symptoms.…”
Section: Discussionsupporting
confidence: 50%
“…Most clinicians today recommend the use of the modified Epley maneuver, the canalith repositioning maneuver (CRM) (Babac and Arsovi c, 2012). This three-position maneuver eliminates the need for sedation and mastoid vibration (Wolf et al, 1999;Babac and Arsovi c, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Epleys therapy was highly effective: success rates were found to be 90.7% after one conductance of an Epley reduction and 96.0% after two conductances. However, this therapy was not appropriate for patients with limited cervical spine motion, who could use the Semont procedure ( 31 ). Anagnostou et al treated 51 PC-BPPV patients each with the Epley procedure or the Semont procedure and found that the successful reduction rate was not significantly different between these two therapies: 7.8% of patients had HC-BPPV after treatment by the Epley procedure, while no patient had HC-BPPV after treatment by the Semon procedure ( 32 ).…”
Section: Manual Reduction Of Bppvmentioning
confidence: 99%
“…This study involved 114 patients which is relatively larger than other similar studies; 60 patients in Panuganti et al study [8], 75 patients in Babac and Arsović study [9], and 62 patients in Khatri et al study [10]. In this study, the patients age ranged from 26 to 64 year (mean 43.2 ± 11.36) with nearly equal presentation in males (52.6%) and females (47.4%) like studies of Suarez et al [11] and Sacco et al [12]; however, in the study of Brevern et al [1], there was a female predominance.…”
Section: Discussionmentioning
confidence: 91%